Peran penyuluh peternakan dalam peningkatan pendapatan anggota kelompok peternak babi di Kecamatan Tompaso Barat Kabupaten Minahasa - Kogoya, Y; Lenzun, G D; Wantasen, E (ZOOTEC, 2021)
THE ROLE OF ANIMAL HUSBANDRY EXTENSION IN INCREASING INCOME OF PIG FARMER GROUP IN WEST TOMPASO DISTRICT, MINAHASA REGENCY.This study aims to see how the responses of farmers to the role ofextension workers in increasing the income of pig farming in Kamanga Village, West Tompaso District, Minahasa Regency. The data sources are primary and secondary. Observation and interview data collection methods. The population of breeders who raise pigs and the number of samples taken are members of the Kamanga Village hog farming group who have received guidance from the Minahasa District Agriculture, Animal Husbandry and Plantation Agency. Result study showed that extension officer from the agricultur and livestockÂ  service have a major roleÂ  in increasing of income of pigs breeders in Kamanga village , Tompaso Sub District